Multiple endocrine defects in adult-onset Sprouty1/2/4 triple knockout mice - Gisela Altés; Anna Olomí; Aida Perramon-Güell; Sara Hernández; Anna Casanovas; Aurora Pérez; Juan Miguel Díaz-Tocados; José Manuel Valdivielso; Cristina Megino; Raúl Navaridas; Xavier Matias-Guiu; Ophir D. Klein; et al. (Scientific Reports, 2024)
Abstract Genes of the Sprouty family (Spry1-4) are feedback inhibitors of receptor tyrosine kinases, especially of Ret and the FGF receptors. As such, they play distinct and overlapping roles in embryo morphogenesis and are considered to be tumor suppressors in adult life. Genetic experiments in mice have defined in great detail the role of these genes during embryonic development, however their function in adult mice is less clearly established. Here we generate adult-onset, whole body Spry1/2/4 triple knockout mice. Tumor incidence in triple mutant mice is comparable to that of wild type littermates of up to one year of age, indicating that Sprouty loss per se is not sufficient to initiate tumorigenesis. On the other hand, triple knockout mice do not gain weight as they age, show less visceral fat, and have lower plasma glucose levels than wild type littermates, despite showing similar food intake and slightly reduced motor function. They also show alopecia, eyelid inflammation, and mild hyperthyroidism. Finally, triple knockout mice present phosphaturia and hypophosphatemia, suggesting exacerbated signaling downstream of FGF23. In conclusion, triple knockout mice develop a series of endocrine abnormalities but do not show increased tumor incidence.